A Mathematical Modeling of Resonances of the Nonlinear Tilted Support Spring System under Harmonic Excitation. (10th September 2013) - Wu, Meiping; Wang, Yun; Zhang, Chaofeng
Abstract : A novel nonlinear tilted support spring damping system is proposed in this paper. The nonlinear dynamic equation is developed under the foundation displacement excitation and the resonance frequency of the system is also analyzed. Furthermore, different support angles affecting the vibration amplitude and the natural frequency of the system are researched. The model of the tilted support spring damping system is analyzed by ANSYS, and modal analysis and harmonic response analysis are made under harmonic excitation. The study shows that the supporting angle makes a great impact on the amplitude of the system and the response amplitude of the system is also reduced with the decrease of support angle. Through the analysis and comparison of the example, it provides a theoretical basis of the analysis for the tilted support spring damping system support angle's optimal design.